Unelected institutions and their role in political decision-making: Russia and Egypt as a model - salman, ayat ahmed (The International and Political Journal, 2025)
This study explores the role of unelected institutions in political decision-making within authoritarian regimes. These institutions—including the military, security agencies, senior bureaucracies, appointed judiciaries, and official religious bodies—serve as key actors in shaping public policy and reinforcing regime durability, often at the expense of popular will. Using analytical frameworks such as elite theory and the concept of the deep state, the research examines the mechanisms through which these institutions exert influence. Case studies from Russia, Egypt illustrate how unelected bodies operate across different authoritarian contexts. The study concludes that such institutions undermine democratic accountability, obstruct political reform, and perpetuate closed and centralized power structures. It recommends strengthening civil society, promoting institutional transparency, and curbing the dominance of unelected actors in governance.